SPATIAL TEMPORAL ANALYSIS OF LAND USE CHANGES IN AREAS VULNERABLE TO EARTHQUAKES AND LANDSLIDES, (Case Study: Cianjur Regency) - Noer, Marwah; Mardalena, Ayu; Astuty, Yulia Indri; Rahmadi, Rahmad; Manessa, Masita Dwi Mandini (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2024)
Cianjur Regency is a regency that is vulnerable to earthquakes and landslides. This is because the Cianjur Regency is crossed by the Cimandiri Fault which is actively moving. Meanwhile, the population growth rate in Cianjur district has increased based on data from Badan Pusat Statistik (BPS) for 2020-2021. Population growth causes many problems, especially the problem of space. Built-up land will be higher as the population increases. This study uses the temporal spatial analysis method of land use with variables of land use in 2013 and 2022, Earthquake Vulnerability Index, and Landslide Vulnerability Index. This variable was obtained based on the processing of Landsat 8 Satellite Imagery data in 2013 and 2022 and disaster vulnerability raster data from Badan Nasional Penanggulangan Bencana (BNPB). The results of this study are a temporal spatial analysis of changes in land use from 2013 - 2022 for earthquake-vulnerable areas and landslide-vulnerable areas. Changes in the use of built-up land to the Landslide Vulnerability Index experienced an increase in area in all categories. In contrast, the Earthquake Vulnerability Index only experienced an increase in the medium and high categories.